2013
DOI: 10.1121/1.4788985
|View full text |Cite
|
Sign up to set email alerts
|

Scattering from suspended sediments having different and mixed mineralogical compositions: Comparison of laboratory measurements and theoretical predictions

Abstract: Laboratory measurements of the acoustic scattering properties of aqueous suspensions of non-cohesive sands having different and mixed mineralogical compositions are presented. Four different types of sand are examined: quartz, crushed shell, magnetite, and muscovite mica. The experimental data obtained for each type of sand are compared with theoretical scattering predictions for spheres having the same physical properties. The results show that for each type of sand, scattering is enhanced in the geometric re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…More generally, the measured values of both n h and K h increase with ka, as expected: in general, n and K are expected to be proportional to (ka) 4 and (ka) 2 , respectively, at low ka (i.e., ka ( 1) and approach constant values at high ka (i.e., ka > 1), where k is the ultrasonic wave number (k ¼ 2p/k) and a is the particle diameter (Thorne and Hanes, 2002). However, the discrepancies between the measured and predicted values of n h are not insignificant, although this conclusion is likely less to be a failure of the mathematical and measurement techniques developed here, but to be due to the potential problems involved in estimating the acoustic properties of particles from the median value (i.e., d 50 ) of measured size distributions (Moate and Thorne, 2013;Thorne and Meral, 2008), and more generally due to the width of the particle size distributions. Factors other than the particle size distribution are present, in particular: differences in density, compressibility and particle shape between the two spherical glass species (Honite) and the two nonspherical plastic species (Guyblast) and quartz sand data of Thorne and Meral (2008) that were used to predict n. Density is accounted for explicitly in the model, through Eqs.…”
Section: Resultsmentioning
confidence: 79%
“…More generally, the measured values of both n h and K h increase with ka, as expected: in general, n and K are expected to be proportional to (ka) 4 and (ka) 2 , respectively, at low ka (i.e., ka ( 1) and approach constant values at high ka (i.e., ka > 1), where k is the ultrasonic wave number (k ¼ 2p/k) and a is the particle diameter (Thorne and Hanes, 2002). However, the discrepancies between the measured and predicted values of n h are not insignificant, although this conclusion is likely less to be a failure of the mathematical and measurement techniques developed here, but to be due to the potential problems involved in estimating the acoustic properties of particles from the median value (i.e., d 50 ) of measured size distributions (Moate and Thorne, 2013;Thorne and Meral, 2008), and more generally due to the width of the particle size distributions. Factors other than the particle size distribution are present, in particular: differences in density, compressibility and particle shape between the two spherical glass species (Honite) and the two nonspherical plastic species (Guyblast) and quartz sand data of Thorne and Meral (2008) that were used to predict n. Density is accounted for explicitly in the model, through Eqs.…”
Section: Resultsmentioning
confidence: 79%
“…This stage of the tidal cycle was chosen as it was observed to produce a high signal to noise ratio with maximum suspended sediment concentrations, as can be seen for example between 10:00 and 11:00 in Figure 7a. Figure 8 shows the resulting K t profiles obtained from the BASSI were nominally invariant with both range and between individual transducers of the same operating frequency, with differences between transducers of the same frequency being of the same order as the uncertainty in laboratory measurements of K t reported elsewhere; ~ 5 % (Moate and Thorne, 2013). Thus, as no significant differences were observed in K t between transducers of the same operating frequency, an overall mean K t was calculated for each operating frequency for each transducer array.…”
Section: Bassi Calibration Profiles and Mean Coefficientsmentioning
confidence: 99%
“…As recent studies have shown that the acoustic properties of sediments are a function of their mineralogical composition Thorne, 2012 and2013), the mineralogical composition of the local sediments was determined via X-ray diffraction (XRD). XRD analysis was undertaken on 5 g sub-samples of the sediment grab samples.…”
Section: Mineralogical Composition and Particle Size Distributionmentioning
confidence: 99%
“…Research has focused (using down-, side-or up-looking ADCP deployment) on the relation of suspended sediment and corrected backscatter (Thorne et al, 1993(Thorne et al, , 1998Reichel and Nachtnebel, 1994;Holdaway et al, 1999;Thorne and Hanes, 2002;Gartner, 2004;Wall et al, 2006;Topping et al, 2007;Deines, 1999;Szupiany et al, 2009;Hanes, 2012;Guerrero et al, 2013Guerrero et al, , 2016Latosinski et al, 2014;Thorne and Hurther, 2014;Landers et al, 2016;Manaster et al, 2016;Venditti et al, 2016;Topping and Wright, 2016;Mullison, 2017;Hackney et al, 2018), acoustic attenuation and scattering properties (Thorne and Meral, 2008;Wright, et al, 2010;Sassi et al, 2012;Moate and Thorne, 2013;Moore et al, 2013;Agrawal and Hanes, 2015;Hanes, 2016;Topping and Wright, 2016;Haught et al, 2017), and acoustic scattering by suspended flocculating sediments (Thorne and Hurther, 2014;Vincent and McDonald, 2015;Thomas et al, 2017).…”
Section: Introductionmentioning
confidence: 99%